Hasdai Crescas on Codification, Cosmology and Creation : The Infinite God and the Expanding Torah - Ackerman, Ari (Supplements to The Journal of Jewish Thought and Philosophy, 2022)
This work focuses on the conception of God of the medieval Jewish philosopher and legal scholar, Hasdai Crescas (1340-1410/11). It demonstrates that Crescas' God is infinitely creative and good and explores the parallel that Crescas implicitly draws between God as creator and legislator, which is rooted in his understanding of the Deity as continuously involved in generative activity through the outpouring of goodness and love as manifest by multiple, simultaneous and successive worlds and a perpetually expanding Torah. It also reviews the Maimonidean background for Crescas' position and suggests that Crescas is countering Maimonides' stance that creation is limited to a single moment and Maimonides' notion of the Torah as perfect and immutable.